Atta Method: A Nature Based Approach - Ecar, Miguel (Anais da Escola Regional de Engenharia de Software (ERES), 2017)
Traditional software engineering approaches were developed based on old manufacturing process, in term of roles, responsibilities, tasks and hierarchy. New approaches, known also as Agile approaches, are based on a fusion of these traditional approaches and the Agile Manifesto, which changes the per- spective of main software process objectives. This paper proposes a new soft- ware engineering method called Atta, based on a nature process. Furthermore this paper explore the main current software approaches and contrast them with the proposed one. The result is a new software engineering method, which has bases on nature and brings a new vision of organizational processes, responsi- bilities, roles and task division. Nonetheless this method needs to be validated.